Tensor product for g-fusion frame in hilbert $C^{*}-$modules - Nhari, fakhr-dine; Rossafi, Mohamed; Aribou, Youssef (Jurnal Matematika, Statistika dan Komputasi, 2023)
In this paper, we stady the tensor product of $g-$fusion frame in Hilbert $C^{*}-$modules and we give the frame operator for a pair of $g-$fusion bessel sequences in tensor product of Hilbert $C^{*}-$modules.